Mirizzi Syndrome: The classic presentation - James G. Glasser, MD, FACS; Ratul Bhattacharyya (Elsevier, 2021)
We recently cared for two children with Mirizzi Syndrome. Our first patient was a 12-year-old girl who had an unusual variant of Mirizzi syndrome: a cholecystohepatic fistula, which we stumbled upon during laparoscopic cholecystectomy [1].The subject of this report is a 14-year-old young lady whose presentation was more typical (textbook). Cystic duct obstruction by an impacted stone caused acute cholecystitis. Because of the proximity of the ducts, the attendant inflammation "spilled over" onto the common bile duct (CBD) and caused partial obstruction. Endoscopic retrograde cholangiopancreatography (ERCP) with stent placement was followed by a laparoscopic cholecystectomy.